(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
Based on the experience developed by the research project Deep Movements, Sound Body, Immensity and Voices, the article discusses the period between 2024.1 and 2024.2. The writing emerges from the reflective and sensitive dive into the laboratory practice, through which the concepts proposed by the research, symbolic contents of the artistic project and transversal knowledge awakened along the way were articulated, whose context of time and space was made during the process of creating the performance show Apas.